The Impact Of Economic Growth On Investment Levels In Indonesia A Meta-Regression Analysis - Aprilya, Jovita Nuril; Rasyid, Mohtar (Lembaga Teewan Journal Solutions, 2026)
This research was conducted to analyze the relationship between economic growth and investment levels in Indonesia using meta regression. This research uses 18 studies published in the period 2016 - 2025. The data used is the GDP coefficient value on investment levels in Indonesia and analyzed using the Random Effects Model via STATA 17 software. The results show the effect size reaches 0.070 with a 95% confidence interval (-0.054 to 0.194). This indicates that economic growth has a positive impact on investment levels in Indonesia, although it is in the low category but is not significant. The results of the meta-regression show that moderating variables such as year, method, gender, and number of observations have a significant influence on the variation in effect size. In addition, the publication bias test using the Egger method showed that there were indications of publication bias, where the probability value obtained was 0.0001 (p < 0.05). Overall, the results of this study indicate that economic growth makes a positive contribution to increasing investment in Indonesia, although this relationship is not always consistent in every study analyzed.